The Effect of Cell Wall Material Strain and Strain-Rate Hardening Behaviour on the Dynamic Crush Response of an Aluminium Multi-Layered Corrugated Core - Güden, Mustafa; Canbaz, İlker; Güden, Mustafa (Taylor and Francis Ltd., 2021)
The effect of the parameters of the Johnson and Cook material model on the direct impact crushing behaviour of a layered 1050 H14 aluminium corrugated structure was investigated numerically in LS-DYNA at quasi-static (0.0048 m s(-1)) and dynamic (20, 60, 150 and 250 m s(-1)) velocities. Numerical and experimental direct impact tests were performed by lunching a striker bar onto corrugated samples attached to the end of the incident bar of a Split Hopkinson Pressure Bar set-up. The numerical impact-end stress-time and velocity-time curves were further compared with those of rigid-perfectly-plastic-locking (r-p-p-l) model. Numerical and r-p-p-l model impact-end stress analysis revealed a shock mode at 150 and 250 m s(-1), transition mode at 60 m s(-1) and quasi-static homogenous mode at 20 m s(-1). The increase of velocity from quasi-static to 20 m s(-1) increased the numerical distal-end initial peak-stress, while it almost stayed constant between 20 and 250 m s(-1) for all material models. The increased distal-end initial peak-stress of strain rate insensitive models from quasi-static to 20 m s(-1) confirmed the effect of micro-inertia. The numerical models further indicated a negligible effect of used material models on the impact-end stress of investigated structure. Finally, the contribution of strain rate to the distal-end initial peak-stress of cellular structures made of low strain rate sensitive Al alloys was shown to be relatively low as compared with that of strain hardening and micro-inertia, but it might be substantial for the structures constructed using relatively high strain rate sensitive alloys.
Keywords: Corrugated core; Direct impact; Modelling; Distal-end; Shock deformation